Haiti: Internal Socio-Historical Aspects and Emigration - Pinto, Simone Rodrigues (2019)
Haiti, a state constitutionally founded in equality between blacks and whites, lives in daily life a cruel racial division between blacks and mulattoes, a complex relationship with foreigners, and despite immense geographic and cultural wealth, the institutional weakness and corruption paralyze its development. This text proposes a brief socio-historical analysis, chronologically and linearly explained to facilitate the chain of events, in order to provide support for the understanding of some of these paradoxes and the reasons for the large number of Haitians emigrating from this country.